Facile Synthesis of Bioactive 4H-[1,4]-Benzothiazines Under Solvent Free Conditions - Kalwania, G.S.; Chomal, S.; Choudhary, Savita (Asian Journal of Chemistry, 2011)
An efficient method for synthesis of 4H-[1,4]-benzothiazines under solvent free conditions has been developed. The oxidative condensation of 2-aminobenzenethiols with β-diketones/β- ketoesters in presence of catalytic amount of hydrazine hydrate yields the 4H-[1,4]- benzothiazines. The reaction is accelerated by microwave irradiation under solvent free conditions in presence of an energy transfer agent DMF to get the product in high yield. The 2- aminobenzenethiazole required for the synthesis of 4H-[1,4]-benzothiazines are also obtained by a new method instead of presently used time consuming and low yielding method. The structure of the synthesized compounds has been characterized by IR, NMR, mass spectral studies and elemental analysis.